I Saw Ramallah - Ariege Muallem (International Institute of Islamic Thought, 2001)
I Saw Ramal/ah is about Barghouti's much-awaited journey to his homeland after thirty years of exile. The book is rich with personal memories of places, people, towns, events and times both in the past and present and is full of humor, laughter, joy, sadness, heartbreak, sacrifice and mourning. Throughout the book, there is a haunting feeling of loss and loneliness as a result of dispossession. The book starts at the bridge between Jordan and Palestine, the very bridge that Barghouti had innocently crossed thirty years ago in order to reach Cairo to continue his studies. When war broke out in 1967, he was still in Cairo and could not return. He remembers that day in 1967 very vividly, since it was to mark the beginning of a new life for him, as all of a sudden he was "struck by displacement." One wonders if he would have remembered the details as intensely were it just another day in his normal life and not a day that would mark the beginning of life as an exile. Barghouti jumps from his present to the past and back, cleverly and smoothly, revealing a little here and there, and beckoning the reader to hasten eagerly through the pages to discover the rest of the story. After a ...